An Impulsively Controlled Three-Species Prey-Predator Model with Stage Structure and Birth Pulse for Predator. (14th July 2015) - Hu, Yanyan; Yan, Mei; Xiang, Zhongyi
Abstract : We investigate the dynamic behaviors of a two-prey one-predator system with stage structure and birth pulse for predator. By using the Floquet theory of linear periodic impulsive equation and small amplitude perturbation method, we show that there exists a globally asymptotically stable two-prey eradication periodic solution when the impulsive period is less than some critical value. Further, we study the permanence of the investigated model. Our results provide valuable strategy for biological economics management. Numerical analysis is also inserted to illustrate the results.